ISOLATION, IDENTIFICATION AND USE OF STRAINS OF BACTERIA OF THE GENUS BACILLUS IN A MICROBIOLOGICAL TEST FOR THE DETERMINATION OF ANTIBIOTICS IN MILK - Aktayeva , S.; Kiribayeva , A.; Makasheva , D.; Astrakhanov , M.; Tursunbekova , A.; Baltin, K.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2022)
The use of antibiotics in the treatment of livestock has increased the productivity of the meat and dairy industry. The flip side of the effectiveness of drugs of this group is the presence of side effects, which have caused concern about the widespread use of antibiotics and cause the need to control the residual content of antibacterial agents in dairy products. From soil samples collected in 7 regions of Kazakhstan, 14 microbial isolates were isolated and identified as B. licheniformis, B. sonorensis, B. cereus, B. simplex, B. thuringiensis, B. pumilis, B. mojavensis, B. subtilis, B. atrophaeus, B. paralicheniformis. Sensitivity testing of the isolated strains showed that the strains were susceptible to 13 antibiotics belonging to lincosamide, ansamycin, quinolone, macrolide, fluoroquinolone, tetracycline, nitrobenzene, aminoglycoside, glycopeptide and beta-lactam antibiotics. The proteolytic strain Bacillus licheniformis T7 seems promising as a test culture. It is highly sensitive to antibiotics, grows rapidly on a variety of nutrient media, is alkaline and spore-forming and can be cultured at 37-55°C. The peculiarity of the strain to change the pH of the medium from 5.0 to 7.0 and above makes it possible to use bromcresol purple as a growth-detecting dye. This has been shown in experiments using antibiotic milk samples on LB agar and LB broth pH 5.0. In the absence of growth-inhibiting antibiotics, the culture of B. licheniformis T7 grows vigorously, which causes a pH shift to 7.99 and causes the color of bromocresol purple to change from yellow to purple. The results showed promise for the strain Bacillus licheniformis T7 to be used as a bacterial culture in the development of a microbiological test for the detection of antibiotics in milk.